86.4k views
5 votes
Using the function attached.
Find (f+G)(x)

Using the function attached. Find (f+G)(x)-example-1

1 Answer

3 votes

We have been given two functions
f(x)=-8x^3+5x^2+7x+4 and
g(x)=8x^3-2x+3. We are asked to find
(f+g)(x).

We will use composite function property
(f+g)(x)=f(x)+g(x) to solve our given problem.


(f+g)(x)=-8x^3+5x^2+7x+4+8x^3-2x+3

Now we will combine like terms as:


(f+g)(x)=-8x^3+8x^3+5x^2+7x-2x+4+3


(f+g)(x)=5x^2+5x+7

Therefore, the value of
(f+g)(x) would be
5x^2+5x+7.

User William Gross
by
5.0k points